Plasma Tie2 is a tumor vascular response biomarker for VEGF inhibitors in metastatic colorectal cancer. Issue 1 (December 2018) - Jayson, Gordon; Zhou, Cong; Backen, Alison; Horsley, Laura; Marti-Marti, Kalena; Shaw, Danielle; Mescallado, Nerissa; Clamp, Andrew; Saunders, Mark; Valle, Juan; Mullamitha, Saifee; Braun, Mike; et al.
Abstract Oncological use of anti-angiogenic VEGF inhibitors has been limited by the lack of informative biomarkers. Previously we reported circulating Tie2 as a vascular response biomarker for bevacizumab-treated ovarian cancer patients. Using advanced MRI and circulating biomarkers we have extended these findings in metastatic colorectal cancer (n = 70). Bevacizumab (10 mg/kg) was administered to elicit a biomarker response, followed by FOLFOX6-bevacizumab until disease progression. Bevacizumab induced a correlation between Tie2 and the tumor vascular imaging biomarker, K trans (R :−0.21 to 0.47) implying that Tie2 originated from the tumor vasculature. Tie2 trajectories were independently associated with pre-treatment tumor vascular characteristics, tumor response, progression free survival (HR for progression = 3.01, p = 0.00014; median PFS 248 vs. 348 daysp = 0.0008) and the modeling of progressive disease (p < 0.0001), suggesting that Tie2 should be monitored clinically to optimize VEGF inhibitor use. A vascular response is defined as a 30% reduction in Tie2; vascular progression as a 40% increase in Tie2 above the nadir. Tie2 is the first, validated, tumor vascular response biomarker for VEGFi. Identification of response biomarkers is a key step towards the development of personalised care. Here, Jayson et al. identify plasma Tie2 as a biomarker for the response of the tumor vasculature to anti-angiogenics in patients with metastatic colorectal cancer, suggesting that monitoring Tie2 levels may help guide therapy in the clinics.